2007
DOI: 10.1002/pbc.20640
|View full text |Cite
|
Sign up to set email alerts
|

Remission of aplastic anemia induced by treatment for Graves disease in a pediatric patient

Abstract: Aplastic anemia (AA) is mediated by T-cell autoimmunity in the majority of cases; it is rare and mostly idiopathic in children. We describe a child, who developed AA following Graves' disease which could not be attributed to antithyroid drugs. We hypothesized that both diseases were caused by similar autoimmune process. We monitored the blood counts and did not administer any conventional treatment for AA assuming that the existing anti- hematopoietic stem cell humoral and cellular immunity might subside with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…In autoimmune diseases, ACD is the main mechanism of anaemia, although this can also be caused by other mechanisms such as iron deficiency or drug effects 43 . In addition, autoimmune disorders can be associated with pure red cell aplasia, 44,45 aplastic anaemia, 46 haemophagocytic syndrome 47 and autoimmune myelofibrosis 48 . Although anaemia in chronic kidney diseases can be the result of inflammatory changes and ACD, it could also be due merely to a poor production of erythropoietin.…”
Section: Anaemia Of Chronic Disease/anaemia Of Chronic Inflammationmentioning
confidence: 99%
“…In autoimmune diseases, ACD is the main mechanism of anaemia, although this can also be caused by other mechanisms such as iron deficiency or drug effects 43 . In addition, autoimmune disorders can be associated with pure red cell aplasia, 44,45 aplastic anaemia, 46 haemophagocytic syndrome 47 and autoimmune myelofibrosis 48 . Although anaemia in chronic kidney diseases can be the result of inflammatory changes and ACD, it could also be due merely to a poor production of erythropoietin.…”
Section: Anaemia Of Chronic Disease/anaemia Of Chronic Inflammationmentioning
confidence: 99%
“…The fact that pancytopenia resolved with reversal of hyperthyroidism in all the reported cases including our case provides ample testimony to the causal relationship between the two conditions. In all, except one case of aplasia, reported by Das et al, 4 the bone marrow was hypercellular. Hematologically, pancytopenia in the presence of a hypercellular marrow could be related to either of the three mechanisms, either organ sequestration such as observed in hypersplenism, an enhanced removal of peripheral circulating blood cells by an immune or toxic mechanism, or hemopoietic stem cell dysfunction such as myelodysplasia.…”
Section: Discussionmentioning
confidence: 84%
“… 2 Das et al reported a case of remission of aplastic anemia induced by treatment of Graves’ disease in a pediatric patient. 4 Kebapcilar et al reported a case of recovery from pancytopenia and liver dysfunction after administration of propylthiouracil for Graves’ disease. 7 Lima et al reported 4 patients with Graves’ disease who presented with pancytopenia at diagnosis, three of whom recovered on antithyroid drug therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these observations both hyperthyroidism and autoimmunity contribute to the pathogenesis of pancytopenia in GD patients. Bone marrow biopsy can be hypercellular [14, 15] or normocellular [17, 19] (like our patient) and theories such as organ sequestration, decreased peripheral circulation times, stem cell dysfunction, and nutritional deficiencies have been suggested.…”
Section: Discussionmentioning
confidence: 96%
“…Using these in a patient with pancytopenia can be challenging. However, the published cases in the literature have almost universally responded well to treatment with these medications, and reaching euthyroid status has been the key for correction of the hematologic abnormality [1419]. This has also been true in cases of patients with autoimmune hemolytic anemia and Evan's syndrome [8–12].…”
Section: Discussionmentioning
confidence: 99%